Impact of Workplace Harassment on Internship Satisfaction as Perceived by Human Resource Management Interns of the University of Kelaniya - Gunawardhana, D. S. W.; Devadas, U. M. (Faculty of Commerce and Management Studies, University of Kelaniya Sri Lanka, 2022)
In today's challenging and competitive employment system, the University continuously strives to increase student internship satisfaction. There the relationship between internship satisfaction and workplace harassment of those students was analyzed. A pattern of unwanted behaviour meant to frighten, insult, degrade, or humiliate a person or group of people is called workplace harassment. It is a sign of dominance (Somasundaram & Aswathy, 2022) . The feelings or overall attitude that interns have toward their jobs and elements associated with their jobs, such as the workplace, working conditions, fair compensation, and contact with partners, is known as internship satisfaction (Anwar & Louis, 2017) .The current study was initiated to identify the impact and relationship between workplace harassment on internship satisfaction as perceived by human resource management interns of the university of Kelaniya. The study is limited to the identification of the factors of the human resource management interns of the University of Kelaniya, Sri Lanka. This study followed a quantitative approach and cross-sectional field study, furthermore, used the deductive methods of research. Usable questionnaires were received from 120 respondents. Data were analyzed using SPSS. According to regression analysis, results indicate that learning styles significantly impact undergraduates’ academic performance by 8.9%. Correlation analysis results indicate that there is a significant relationship between workplace harassment and internship satisfaction. Workplace harassment is an effective way in developing an intern’s internship satisfaction. The present study could facilitate and provide a guideline to consider the implementation of practical applications regarding enhancing the undergraduates’ internship satisfaction. The findings of the study s indicate that workplace harassment significantly impacts undergraduate internship satisfaction in the human resource management undergraduates of the University of Kelaniya. In a conclusion, the current study concludes by declaring that workplace harassment significantly impacts to undergraduates’ internship satisfaction.
Keywords: Workplace Harassment, Internship Satisfaction